Criminal Sanctions for Persecution Resulting in Serious Injury - Fandaria Putri Yasin; Fence M. Wantu (Universitas Negeri Gorontalo, 2022)
This study aims to find out and analyze how to prove the verdict of a criminal offense that results in serious injury based on the title raised in this authorship. An author is a type of writer an Emperis law or a field writer. With a Case approach. The process of collecting data from regulations and other references related to the problem being studied. The results of this author show that the proof of the Determination of the criminal act of assault resulting in serious injury is said to be incorrect but if we refer to the court decision of the defendant/convicted person is proven to have committed a criminal act of assault resulting in serious injury, but is only sentenced to imprisonment for six (6) months. The judge’s role in determining the criminal act of assault resulting in serious injury is influenced by two counts, namely the judge's estimate that lawfully and convincingly committed the crime of persecution and the legal act used in the indictment article is more than Article 351 Paragraph 2 of the Criminal Code of persecution resulting in serious injury.